Evaluation of data sets usable for validating multiaxial fatigue strength criteria. (April 2021) - Papuga, Jan; Kaľavský, Adam; Lutovinov, Maxim; Vízková, Ivona; Parma, Slavomír; Nesládek, Martin
Highlights: Rules for defining experimental data sets for validating multiaxial fatigue criteria. Multiaxial fatigue criteria and their inputs discussed. Various experimental setups in multiaxial high-cycle fatigue discussed. List of data sets rejected from being included in the verification set published. List of data sources usable for such verification published. Abstract: This paper attempts to establish clear rules for evaluating available experimental data that could be used for validating multiaxial fatigue strength criteria. The goal of these rules is to identify and eliminate experimental data that could lead to erroneous conclusions, that would hide otherwise visible trends or that would result in non-correct bias. Various reasons for rejecting specific data sets are provided and substantiated. Two appendices list references to sources of data that were not accepted as credible (Appendix A), and to data which were accepted as credible (Appendix B) for inclusion in the final benchmark set.